Thiazole inhibitors of α-glucosidase: Positional isomerism modulates selectivity, enzyme binding and potency of inhibition. (June 2022) - Ghani, Usman; Ashraf, Sajda; Haq, Zaheer Ul; Kaplancikli, Zafer Asim; Demirci, Fatih; Özkay, Yusuf; Afzal, Sibtain
Abstract: Isomerism plays a key role in determining potency, selectivity and type of inhibition exhibited by enzyme inhibitors. We present 20 new benzylidene-hydrazinyl-thiazole inhibitors of α-glucosidase featuring positional isomerism of the methyl group at 3 and 4 positions of their piperidine ring. This structural property helped understand their potency and selectivity to the enzyme yielding new clues to α-glucosidase inhibition. The isomerism was pivotal to improving or deteriorating enzyme binding and potency of inhibition shown by the target compounds. Data from enzyme kinetics experiments were in agreement with docking and molecular dynamics simulations revealing a direct influence of isomerism on enzyme-inhibitor molecular interactions. Generally, the 4-methyl derivatives showed more selectivity toward the enzyme since they established more and stronger molecular contacts with the enzyme than their 3-methyl counterparts. However, the isomerism did not significantly affect the type of inhibition since majority of the compounds exhibited noncompetitive enzyme inhibition except for one. Our work provides essential and interesting clues to understanding α-glucosidase inhibition by thiazole isomers that would help explore new avenues to designing and developing better α-glucosidase inhibitors as antidiabetic drugs. Graphical Abstract: ga1 Highlights: Positional isomerism plays a key role in determining alpha-glucosidase inhibition. The 4-methyl isomers are more selective to the enzyme than their 3-methyl counterparts. The isomerism did no influence the type of enzyme inhibition.